Pengaruh Faktor Sosial Demografi Terhadap Remitan Pekerja Migran Nonpermanen Asal Luar Bali Di Kota Denpasar - Andharista, Ni Putu Mita; Sudibia, Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
Remittance is one way to keep migrant workers can establish the relationship with their families in their homeland. Remittances can also help improve the economy of the family as well as their areas of origin, remittances not just remittances, but remittances can also be ideas, goods can be shipped to their home area. The purpose of this study was to determine the direct effect of education, length of employment, marital status and income of the remittances of migrant workers nonpermanen from outside Bali in Denpasar, and the indirect effect of education, length of employment and marital status on the remittances of migrant workers nonpermanen from outside Bali through income , The analysis showed education, length of employment, marital status and income significantly influence nonpermanen remittances of migrant workers. Revenue is mediating variable between education, length of employment and worker remittances migrna nonpermanen. Income is not a mediating variable between marital status and non-permanent migrant worker remittances.
Keywords: Education; length of employment; marital status; income; remittances